Efektywność i sprawiedliwość jako przesłanki budowy racjonalnego systemu opodatkowania dochodów osób fizycznych - Kumor, Ewelina (Fairness and Efficiency as Aspects of Formation Rational Personal Income Tax Rate, 2009)
Tax systems existing in Europe are progressive and largely destined to finance redistribution programmes. Existing tax systems are far from being efficient and just. The question is what can be done to approach the desired state of affairs in which the taxes are low, equal, simple and thus more just. Tax system must be based on clear principles. Tax should be simple and understandable, stable, predictable, adequate, efficient and fair. Taxes should be based on ability to pay. A tax system should be aligned with the economic goals of the jurisdiction imposing the tax
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 142-149